(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2025)
Inadequate housing for foreign workers has long been a hallmark of the global housing crisis. While the right to adequate and safe housing is a fundamental human right, access to such housing for foreign workers is heavily influenced by the regulations of the destination country and warrants careful attention. This study explores the issues and challenges related to the provision of accommodation for foreign workers in Malaysia from a legal perspective, focusing on Section 24H of the Employees’ Minimum Standards of Housing, Accommodations and Amenities Act 1990 (Act 446), a statutory provision that employers or Centralised Labour Quarters (CLQ) provider must comply with. The research employs a qualitative methodology, analysing primary and secondary data sources, including books, journals, official government reports, and news articles. Semi-structured interviews with open-ended questions were also conducted with enforcement officers from relevant agencies and industry players, such as employers in the service and construction sectors. The findings reveal that Malaysia has a well-established legal framework governing the provision of worker accommodation, encompassing national, state, and local-level legislation. The study proposes improvements to existing laws, regulations, and policies as a solution. Keywords: Challenges, human rights, employees’ accommodation, foreign workers’ rights, amendment of Act 446, state and local government law Full Text: PDF